1987
DOI: 10.3109/00016488709109048
|View full text |Cite
|
Sign up to set email alerts
|

The Change in the Electrical Resistance of the Scala Media Produced by Vasopressin

Abstract: The electrical resistance of the scala media (Rm) in the basal turn of the guinea pig was measured during perilymphatic perfusion with vasopressin. As the endocochlear potential (EP) diminished under the influence of vasopressin (0.1 mM), so the Rm increased. The Rm decreased when the EP decreased by vasopressin recovered above the pre-asphyctic level after the termination of temporary asphyxia. The present study demonstrates that the EP decrease produced by vasopressin is associated with the increase in Rm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, the difference in the re sponse of the EP to asphyxia between vaso pressin and furosemide [2,6] suggests that vasopressin changes the EP via another mechanism than furosemide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the difference in the re sponse of the EP to asphyxia between vaso pressin and furosemide [2,6] suggests that vasopressin changes the EP via another mechanism than furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…Second, vasopressin changes the permeabil ity of the cochlear duct to K+, resulting in decrease in K+ concentration and EP. Mori et al [2] have shown that vasopressin pro duced an increase in the electrical resistance of the scala media corresponding closely to the change in EP. This refutes the EP de crease induced by vasopressin being due to breaks in the electrical insulation of the scala media resulting from the increase in the per meability of the cochlear duct to the electro lytes and favors the First possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the intensities and durations of acoustic stimuli would cause fluctuations in endolymph cation composition in the absence of the regulation of rates of secretion and/or absorption. Ionic homeostasis in endolymph is known to be under the control of several extracellular hormones (Mori et al, 1987;Pitovski et al, 1993;Wangemann et al, 2000), including purinergic receptors (Järlebark et al, 2000;Marcus et al, 2005).…”
Section: Introductionmentioning
confidence: 99%